Mortality differentials in the Czech Republic during the post-1989 socio-political transformation - Dzúrová, D (Health & place, 2000)
The Czech Republic, together with Slovakia and Poland, forms a region within Central-Eastern Europe in which the values of life expectancy at birth have been increasing during the period of transformation. However, the tempo of mortality reduction has differed spatially within the territory of the Czech Republic, as have other outcomes of the transformation process. This paper discussed possible socio-economic explanations of regional differences in the tempos of mortality change between 1990/91 and 1995/96. Standardized mortality rates for males aged 0-64 years specified for the three most frequent causes of death were examined by means of the regression and correlation analysis.
Keywords: mortalita; politika; kojenec; mladiství; Česká republika; Socioeconomic Factors; politické systémy; Middle Aged; naděje dožití; mužské pohlaví; Small-Area Analysis; Infant; Adult; Czech Republic; dítě; Politics; Child; socioekonomické faktory; Infant, Newborn; Child, Preschool; novorozenec; Humans; předškolní dítě; Political Systems; zeměpis; Mortality; Life Expectancy; lidé středního věku; dospělí; Geography; Adolescent; analýza malých oblastí; lidé; Male